Older People in the Context of COVID-19: A European Perspective. Issue 8 (16th November 2020) - Pentaris, Panagiotis; Willis, Paul; Ray, Mo; Deusdad, Blanca; Lonbay, Sarah; Niemi, Mia; Donnelly, Sarah
ABSTRACT: The Coronavirus pandemic and associated measures for the protection of the public have impacted differently on different parts of the population and across different nations. In many areas, COVID-19 has also either exacerbated already existing or created new inequalities in relation to specific parts of the population. Older individuals are one group in society that has been widely impacted, while social isolation/shielding measures have placed them in higher risk of loneliness, isolation, financial deprivation and mental health challenges, to name a few. This commentary reflects on such inequalities across four European nations (the United Kingdom (UK), Republic of Ireland, Finland, Spain) and draws attention to the critical role of Gerontological Social Work (GSW), while emphasizing the ways in which social work can intervene. First, we identify common concerns for the rights of older people that span across all four nations, and second, we identify significant roles for GSW practitioners at the individual, community and policy levels and conclude with a call for GSW in these four nations to be reimagined in a time of global crisis.